Dêiticos discursivos: um olhar multicultural em Pepetela - Padovani, Micheline Tacia de Brito (2017)
This work is part of the Research Line History and Description of the Portuguese Language of the Program of Postgraduate Studies in Portuguese Language of PUC / SP. It presents as a theme: The speech of Pepetela and the representation of the Angolan universe based on literary text "The plateau and the steppe", 2009, published in the post-independence period of Angola. The author writes a literature that is committed to the Angolan historical context, its history makes reference to the social context of the country (Angola), demonstrating through the discourse how it was for the Angolan people to go through the process of independence of the Portuguese yoke (1961-1975) , The post-colonization period and the civil war (1975-2002) and the search of the people for their national identity, reconstructing a new history. Thus, the discussion of this theme is relevant, since it seeks to identify on which aspects the Portuguese Language assists in the historical process and the formation of national identity of the Angolan people. Thus, we explain some characteristics regarding the narrative and the particularities of the characters, because the work serves as an instrument to understand the multiculturality and the identity construction of the Angolan man. It is also worth mentioning that the Angolan novel is a meeting point for several discourses, various cultures, various ethnic groups, languages, because in Angola besides the Portuguese language other national languages are spoken and, in the context described by Pepetela, Languages of other nations. With this, we can say that literature is a comprehensive and interactive space between the subject enunciator (subject of writing), the enunciative and the historical texts that go through the narrative